Transformasi Pendidikan Pesantren di Era Modern - Husen Nurcholis Ridwan; Dika Sofyan; Faruq Naufal Purnama (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Pesantren in Indonesia play a crucial role in Islamic religious education. However, amidst the advancement of the times and the challenges of globalization, pesantren are faced with the need to transform in order to remain relevant. This journal aims to analyze the transformation of pesantren education, particularly in integrating religious education and general knowledge in the modern era. The method used is a descriptive qualitative approach with literature studies, relying on data from books, articles, and related journals. The research results show that modern pesantren have adopted curriculum changes by integrating religious subjects and general science, including the use of technology in the learning process. In addition, the introduction of practical skills and entrepreneurship has also become an essential part of preparing students to face global challenges. This transformation not only affects the quality of education but also its impact on society, which increasingly recognizes the importance of pesantren education in producing qualified young people who are ready to compete in the global world. This journal concludes that pesantren who successfully adapt to the advancement of the times have a vital role in creating competent and competitive human resources.